2015
DOI: 10.1039/c5fo00410a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of in vitro gastrointestinal digestion on the anti-inflammatory activity of Vitis vinifera L. leaves

Abstract: Botanicals are widely consumed all over the world for health purposes, with increased usage in the general population, in many different types of products, including foods and plant food supplements. Several reports support for the beneficial effects of botanicals against gastrointestinal inflammation. However, no studies regarding the anti-inflammatory activity in the gastrointestinal tract of red vine leaves have been reported so far. The present work investigates the biological activity of Vitis vinifera L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 40 publications
3
48
0
1
Order By: Relevance
“…Caftaric acid provide protection against the gastrointestinal inflammation (Sangiovanni et al, 2015). Peak 4 was tentatively identified as kaemferol-3-feruloylsophoroside-7-glucoside with characteristics λmax of 320 and 268 nm and was identified from the literature (Santos et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Caftaric acid provide protection against the gastrointestinal inflammation (Sangiovanni et al, 2015). Peak 4 was tentatively identified as kaemferol-3-feruloylsophoroside-7-glucoside with characteristics λmax of 320 and 268 nm and was identified from the literature (Santos et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…As reported in the literature, all these compounds contribute to some positive effects on human health, such as antioxidant and anti-inflammatory activities [14,18]. Indeed, procyanidins have shown to inhibit Interleukin-8 release at gastric level [6].…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 95%
“…The method was validated according to the FDA Guidelines on Bioanalytical Methods Validation [13] and recently published [3,14]. Figure 2 shows that the total phenolic content (TPC) of hydro-alcoholic extracts (HE) was higher than that measured in samples extracted in water (WE).…”
Section: Quantitative Analysis By High Performance Liquid Chromatogramentioning
confidence: 99%
“…It is suggested that quercetin glycosides are more responsible than anthocyanins for this antiinflammatory effect and that this effect is less apparent after gastric digestion. However, its antiinflammatory effect was lost after intestinal digestion; this may be related to its degradation and loss of its biological activity in the gut (Sangiovanni et al, 2015).…”
Section: Pharmacological Effectsmentioning
confidence: 99%